The Effect of Geranylgeraniol and Ginger on Satellite Cells Myogenic State in Type 2 Diabetic Rats - Nigel C. Jiwan; Casey R. Appell; Raoul Sterling; Chwan-Li Shen; Hui-Ying Luk (Current Issues in Molecular Biology)
Type 2 diabetes (T2D) is associated with increased inflammation and reactive oxygen species (ROS) in muscles, leading to basal satellite cell (SC) myogenic impairment (i.e., reduction in SC pool), which is critical for maintaining skeletal muscle mass. T2D may contribute to muscle atrophy, possibly due to reductions in the SC pool. Geranylgeraniol (GGOH) and ginger can reduce inflammation and enhance SC myogenesis in damaged muscles, thereby alleviating muscle atrophy; however, their effect on basal SC myogenic state and muscle mass in T2D rats is limited. Rats consumed a control diet (CON), high-fat diet with 35 mg/kg of streptozotocin (HFD), a HFD with 800 mg/kg body weight of GGOH (GG), or a HFD with 0.75% ginger root extract (GRE). In the eighth week, their soleus muscles were analyzed for Pax7, MyoD, and MSTN gene and protein expression, SC myogenic state, and muscle cross-sectional area (CSA). The HFD group had a significantly lower number of Pax7+/MyoD− and Pax7+/MSTN+ cells, less Pax7 and MyoD gene expression, and less MyoD and MSTN protein expression, with a smaller CSA than the CON group. Compared to the GG and GRE groups, the HFD group had a significantly lower number of Pax7+/MSTN+ cells, less MyoD protein expression, and smaller CSA. The GRE group also had a significantly lower number of Pax7−/MyoD+ and greater MSTN protein expression than the HFD group. Nevertheless, the CON group had a significantly greater number of Pax7+/MyoD− than the GG and GRE groups, and a greater number of Pax7−/MyoD+ cells than the GRE group with a larger CSA than the GG group. GGOH and ginger persevered muscle CSA, possibly through increased MyoD and the ability to maintain the SC pool in T2D rats.